2018
DOI: 10.3390/f9050267
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change-Induced Shift of Tree Growth Sensitivity at a Central Himalayan Treeline Ecotone

Abstract: Himalayan treelines are exposed to above average climate change impact, resulting in complex tree growth-climate relationships for Himalayan Silver Fir (Abies spectabilis (D. Don) Spach) at central Himalayan treelines. The majority of recent studies detected current tree growth sensitivity to dry conditions during pre-monsoon seasons. The aim of this study was to analyze growth-climate relationships for more than a century for a treeline ecotone in east-central Nepal and to test for Blue Intensity (BI; used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 122 publications
3
28
2
1
Order By: Relevance
“…Although the used CRU database has a wide spatial resolution incapable of capturing the wide climate variability between valleys and elevation in the Himalayan region (Schwab et al. , 2018), we found that tree rings encoded a few significant signals of climate variability. Betula utilis was more sensitive than Abies spectabilis to precipitation during the driest months of the year (from October to April), i.e.…”
Section: Discussionmentioning
confidence: 61%
“…Although the used CRU database has a wide spatial resolution incapable of capturing the wide climate variability between valleys and elevation in the Himalayan region (Schwab et al. , 2018), we found that tree rings encoded a few significant signals of climate variability. Betula utilis was more sensitive than Abies spectabilis to precipitation during the driest months of the year (from October to April), i.e.…”
Section: Discussionmentioning
confidence: 61%
“…In the Baltic Sea region, summer moisture availability became increasingly important for the growth of oak (Quercus robur) and European beech (Fagus sylvatica) in the latter 20th century [26]. Increasing growth sensitivity to spring season moisture availability or drought conditions is becoming predominant during recent years for the Abies spectabilis and other conifer species in the central and western Himalaya, along with weakening responses to growing season temperatures [59][60][61]. Radial growth of Fokienia hodginsii in southwest China shows increasing responses to summer temperature (negative) and precipitation (positive) under a warming and drying climate [62].…”
Section: Temporal Shift Of Growth-climate Sensitivitymentioning
confidence: 99%
“…This may predispose these regions for conservation purposes (Fahr & Kalko, 2011), as high habitat heterogeneity provides different niches and resources for a broad range of species (Tews et al., 2004), resulting in different ecological strategies. At the same time, these regions can be very sensitive to global and local changes, especially due to climate, which affects distribution patterns of species, habitats or ecosystem types (Oliveras & Malhi, 2016; Schwab et al., 2018). For example, cold temperatures are an important environmental filter in savanna–forest boundaries in Brazil, limiting the distribution of tree species (Hoffmann et al., 2019).…”
Section: Introductionmentioning
confidence: 99%